2014
DOI: 10.1039/c4an01184h
|View full text |Cite
|
Sign up to set email alerts
|

Performance metrics based on signal intensity for ion mobility spectrometry – based explosive trace detectors using inkjet printed materials

Abstract: Commercial off-the-shelf (COTS) explosive trace detectors (ETDs) have become an integral part of security practices aimed at protecting the public, transportation, and facilities. Despite their widespread deployment, quality control procedures that can evaluate day-to-day instrument performance or differences among units of the same manufacture are in need for development. In this work, we describe the preparation of test materials (TMs) using inkjet printing that have fixed dosing levels of two explosives; 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 15 publications
0
22
0
Order By: Relevance
“…These explosives have been detected using a range of analytical techniques, including ion chromatography (IC) [1,2], capillary electrophoresis (CE) [3,4], high performance liquid chromatography (HPLC) [5], and most notably, ion mobility spectrometry (IMS) [6][7][8][9][10][11][12][13] and mass spectrometry (MS) [14][15][16][17][18][19][20][21][22]. The rapid analysis times and cost effectiveness of these field compatible instruments have led to widespread deployment of ion mobility spectrometry.…”
Section: Introductionmentioning
confidence: 99%
“…These explosives have been detected using a range of analytical techniques, including ion chromatography (IC) [1,2], capillary electrophoresis (CE) [3,4], high performance liquid chromatography (HPLC) [5], and most notably, ion mobility spectrometry (IMS) [6][7][8][9][10][11][12][13] and mass spectrometry (MS) [14][15][16][17][18][19][20][21][22]. The rapid analysis times and cost effectiveness of these field compatible instruments have led to widespread deployment of ion mobility spectrometry.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the laboratory instrument’s amplitude adjusted response to the calibrant was measured 25% higher than the deployed instrument and ~18% RSD across both instruments (less than the >30% RSDs for explosives RDX and PETN previously measured across multiple (16) deployed instruments). 21 Though ambient/environmental conditions of the deployed instrument have the potential to introduce variability in the IMS response and even the calibrant response, the calibration correction (Figure S-2) and intensity (Figure S-3 and S-4) for the instrument was monitored and remained relatively stable across the multiyear period of sample collection, showing no systematic drift in response. In addition, previous work comparing the responses of multiple deployed commercial instruments found no correlation between response and environmental conditions (e.g., temperature or humidity).…”
Section: Resultsmentioning
confidence: 98%
“…In addition, previous work comparing the responses of multiple deployed commercial instruments found no correlation between response and environmental conditions (e.g., temperature or humidity). 21 Finally, previous long-term studies of laboratory and deployed instruments found response variability (relative standard deviation) was derived from the technology limitations and instrument manufacture, as opposed to environmental contamination. 21 …”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…For bulk detection, ideally materials would be detected and identified prior to use in terrorist activities. Towards this end, traditional bulk detection has been achieved via X-ray based instrumentation 43 , trained animals 45 , ion mobility spectroscopy [46][47][48][49] , terahertz spectroscopy, chemical sensors 50 and optical sensors. Typically at checkpoints, materials (less than bulk quantity) are tested for and collected via swabbing or vapor accumulation techniques.…”
Section: Introductionmentioning
confidence: 99%